Fully unsupervised inter‐individual IR spectral histology of paraffinized tissue sections of normal colon. Issue 5 (12th February 2016) - Nguyen, Thi Nguyet Que; Jeannesson, Pierre; Groh, Audrey; Piot, Olivier; Guenot, Dominique; Gobinet, Cyril
Abstract : In label‐free Fourier‐transform infrared histology, spectral images are individually recorded from tissue sections, pre‐processed and clustered. Each single resulting color‐coded image is annotated by a pathologist to obtain the best possible match with tissue structures revealed after Hematoxylin‐Eosin staining. However, the main limitations of this approach are the empirical choice of the number of clusters in unsupervised classification, and the marked color heterogeneity between the clustered spectral images. Here, using normal murine and human colon tissues, we developed an automatic multi‐image spectral histology to simultaneously analyze a set of spectral images (8 images mice samples and 72 images human ones). This procedure consisted of a joint Extended Multiplicative Signal Correction (EMSC) to numerically deparaffinize the tissue sections, followed by an automated joint K‐Means (KM) clustering using the hierarchical double application of Pakhira‐Bandyopadhyay‐Maulik (PBM) validity index. Using this procedure, the main murine and human colon histological structures were correctly identified at both the intra‐ and the inter‐individual levels, especially the crypts, secreted mucus, lamina propria and submucosa. Here, we show that batched multi‐image spectral histology procedure is insensitive to the reference spectrum but highly sensitive to the paraffin model of joint EMSC. In conclusion, combining joint EMSC and joint KM clustering by double PBM application allows to achieve objective and automated batched multi‐image spectral histology. Abstract : An automatic multi‐image IR spectral histology for the simultaneous analysis of a set of spectral images is presented. This approach is based on a joint extended multiplicative signal correction to numerically deparaffinize the tissue sections, followed by an automated joint K‐Means clustering using the hierarchical double application of a validity index. Thus, murine and human colon histological structures were correctly identified at both the intra‐ and the inter‐individual levels.